Customized Design of a Proposed Alignment at MAU Yola Campus in Civil 3D Using Nigerian Federal Ministry of Works Highway (FMWH) Manual - Mohammed Yusuf, Yusuf; Liman Tukur, Abdullahi; Wadzani Gadzama, Emmanuel; Umar Abubakar, Abdulhameed (Journal of Advanced Industrial Technology and Application, 2022)
This study is aimed at testing the ability of Civil3D to design a carriageway using FMWH Manual, customizing it to suit that purpose. For this purpose, input commands in Civil3D were modified to reflect and accommodate the guidelines outlined in the manual. The route under consideration is a proposed dual carriageway alignment at Modibbo Adama University (MAU) Yola, Adamawa State in the North Eastern part of Nigeria. Scope of work carried out includes both field work (focusing on route survey) and roadway alignment design, subdivided into route location, data acquisition method and geometric design. Data for this project was obtained directly from the field using conventional ground survey method. Google Earth was used to select preliminary control points, GARMIN GPSMAP64 Hand Held GPS Phone was use to record the easting and northing of the control points onsite which serves as a baseline. Theodolite traversing by an analogue theodolite (Kern-Swiss K1-M 292272) was used to tie the control points and to range intermediate points at 25m interval longitudinally along the centerline and perpendicular offset points that were 6m & 12m on both Left and Right of the Centre. Natural Ground Level (NGL) was established from first principle by taking Field Short Data (FSD) of elevation of established point along the baseline using a dumpy level (SUN DSC232) to obtain the true level of the alignment. Plate vial test was carried out on the instruments to ensure accuracy of data recorded. Reduce level was computed using Microsoft excel and the output was imported into the design software (Autodesk Civil 3D V.2023) as a dot csv (.csv) data file known as PENZD.csv. The design of the alignment was carried out using criteria-based design by applying Federal Republic of Nigeria Federal Ministry of Works Highway Manual Part 1 Design Volume 1 Geometric Design (2013). A simple horizontal circular curve with a radius of 200m was designed at chainage 0+268.55 to 0+290.41 between two tangents. Two Sag curves; a crested-sag curve towards the beginning of the alignment at chainage 0+160.95 and a sag curve towards the ends of the alignment at chainage 0+655.33 were designed for the vertical alignment. A trapezoidal channel with a base-width of 0.5m, top-width of 1.1m & a depth of 0.8m was provided alongside the proposed road alignment to discharge storm water. Volume of earthworks was computed as 5548.18m3, and that of fill was found to be 1688.43m3 with a net cut-volume of 3859.75m3. A single cell box culvert was proposed to be sited at chainage 0+524 to 0+532.5. Equally, a pipe culvert was proposed to be sited at 0+722 to 0+723. The results indicate that the designed alignment was adequate and economical based on the proposed data.